2019 international clinical practice guidelines for the treatment and prophylaxis of venous thromboembolism in patients with cancer. Issue 10 (October 2019) - Farge, Dominique; Frere, Corinne; Connors, Jean M; Ay, Cihan; Khorana, Alok A; Munoz, Andres; Brenner, Benjamin; Kakkar, Ajay; Rafii, Hanadi; Solymoss, Susan; Brilhante, Dialina; Monreal, Manuel; et al.
Summary: Venous thromboembolism (VTE) is the second leading cause of death in patients with cancer. These patients are at a high risk of VTE recurrence and bleeding during anticoagulant therapy. The International Initiative on Thrombosis and Cancer is an independent academic working group aimed at establishing a global consensus for the treatment and prophylaxis of VTE in patients with cancer. The International Initiative on Thrombosis and Cancer last updated its evidence-based clinical practice guidelines in 2016 with a free, web-based mobile phone application, which was subsequently endorsed by the International Society on Thrombosis and Haemostasis. The 2019 International Initiative on Thrombosis and Cancer clinical practice guidelines, which are based on a systematic review of the literature published up to December, 2018, are presented along with a Grading of Recommendations Assessment Development and Evaluation scale methods, with the support of the French National Cancer Institute. These guidelines were reviewed by an expanded international advisory committee and endorsed by the International Society on Thrombosis and Haemostasis. Results from head-to-head clinical trials that compared direct oral anticoagulant with low-molecular-weight heparin are also summarised, along with new evidence for the treatment and prophylaxis of VTE in patients with cancer.